Methyl 3-[(tert-butoxycarbonyl)amino]benzoate - Murugesan Ponmagaram; Krishnan Saranraj; Karuppiah Muruga Poopathi Raja (IUCrData, 2025)
In the extended structure of the title compound, C13H17NO4, molecular pairs are connected via N—H...O and C—H...O hydrogen bonds, generating inversion dimers characterized by R22(10) graph-set motifs. These dimers further associate through N—H...O and C—H...O interactions, forming supramolecular layers lying parallel to the (104) crystallographic plane. Aromatic π–π stacking interactions and C—H...π contacts contribute to the tri-periodic supramolecular architecture.